Exploring Adaptive Governance for Indigenous Peoples: Lessons from Aotearoa New Zealand's Erosion Control Funding Programme. Issue 1 (2nd January 2020) - Sharma-Wallace, Lisa; Velarde, Sandra J.; Edwards, Peter; Warmenhoven, Tui; Pohatu, Pia
Abstract: In this article, we trace the evolution of the Erosion Control Funding Programme (ECFP) on the East Coast of Aotearoa New Zealand to illustrate the importance of indigenous co-development of forest systems for more adaptive governance. The ECFP was originally created to address severe erosion on the East Coast, but uptake of the programme has been slower than planned. We employ an adaptive governance lens to track the progress of the ECFP over time, paying particular attention to its implications for Aotearoa New Zealand's indigenous Māori people. We argue that a key aspect of the programme's underperformance relates to the local and indigenous context that remained largely unaccounted for in the ECFP's design and implementation. Our resulting analysis addresses a critical oversight in adaptive governance theory and practice relating to its treatment of power, history, and context, with important lessons for environmental governance in the East Coast and beyond.